Removal of Methylene blue, Escherichia coli and Pseudomonus aeruginosa by Adsorption Process of Activated Carbon Produced from Moringa oleifera Bark - Md. Shahin Azad; Mohd Sukri Hassan; Syaza Azahari (USIM Press, Universiti Sains Islam Malaysia, 2024)
E-Proceeding Kolokium Siswazah Fakulti Sains Dan Teknologi 2020 (KOSIST 2020) “Synergizing Innovation and Research Through Science and Technology” 9th December 2020 organized by Faculty Science and Technology